Antiphospholipid antibodies do not cause retargeting of placental extracellular vesicles in the maternal body. (February 2022) - Tsai, Bridget W; Lau, Sandy; Paek, Song Yee; Wise, Michelle; Kando, Ian; Stone, Peter; Chen, Qi; Chamley, Lawrence W
Abstract: Antiphospholipid antibodies (aPL) are autoantibodies that cause pregnancy disorders by a poorly defined mechanism that involves the placenta. The human placenta is covered by a single multinucleated cell, the syncytiotrophoblast, which extrudes vast numbers of extracellular vesicles (EVs) into the maternal blood. Extracellular vesicles are tiny packages of cellular material used by cells for remote signalling. In normal pregnancy, placental EVs assist maternal adaptations to pregnancy. We have previously shown that aPL alter the cargo of placental EVs, increasing the load of danger signals. These changes in EV cargo may explain how aPL contribute to the increased risk of recurrent miscarriage, preeclampsia and stillbirths observed in aPL-affected pregnancies. An additional possibility, that aPL alters the targeting of placental EVs to maternal organs to cause maternal maladaptation to pregnancy was investigated in this study. Highlights: Biodistribution of 1st trimester placental EVs was unchanged following aPL treatment. Placental EVs mainly target to the liver 30 min after intravenous injection. Placental EVs also target to the lungs, kidneys and spleen in the same conditions.